The Effectiveness of the SDGs Program on the Welfare of the Pendowolimo Village Community - Rahayuningsih, Eka; Styawati, Endang; Maula, Mila Minhatul (Proceedings of Annual Conference for Muslim Scholars, 2025)
This.study aims to analyze extent to which the effectiveness of the Sustainable Development Goals (SDGs) implementation at the village level can improve community welfare by employing the Maqāṣid al-Sharī’ah approach. The research focuses on Pendowolimo Village, Karangbinangun Sub-district, Lamongan Regency. Design was adopted with a mixed-methods, A comprehensive analysis with combining quantitative and qualitative. This type of research is a Sequential Explanatory design. A stratified random sampling technique. Quantitative data were collected through surveys involving 200 household, qualitative data were in-depth interviews with village officials and beneficiary residents. Statistical analyses included validity tests, reliability tests, t-tests, coefficient of determination (R²) test. The findings indicate that the effectiveness of the Village SDGs program has a significant effect on community welfare, with a value of 0.000 (<0.05), a coefficient of determination (R²) of 0.950, and a correlation coefficient of 0.975. The study further asserts that applying the values of Maqāṣid al-Sharī’ah which encompass the protection of religion, life, intellect, lineage, and property can strengthen the implementation of the Village SDGs, ensuring that they are oriented not only toward material well-being but also toward spiritual and social prosperity.